Motorized Jacquard technology for multilayer weaving damages study and reduction: Shed profile and close shed profile. (March 2019) - Decrette, Mathieu; Osselin, Jean-François; Drean, Jean-Yves
Materials used for composite reinforcements usually have high mechanical performances which are linked to a very sensitive and brittle behaviour to friction. The weaving process applied to delicate yarns, like glass, carbon and some other technical yarns, generate damages which tend to reduce the performances of the final composite. Shedding may be a major weaving stage for the generation of yarn damages. Based on a specific weaving pattern, it was observed that different shedding configurations could influence yarn damages at the shedding step. The specificity of the motorized Jacquard device is used to generate different movements and geometry configurations. A particular methodology needed to be set in order to confirm these observations and bring out a clear effect of shedding parameters on yarn damages. After damages have been identified and classified, some experiments will count the damage occurrences and evolutions in time according to shedding parameters. The aim of this research is first to show a clear effect of shedding on warp damaging thanks to the quantification of damages and then to set out an optimized configuration of shedding parameters which may reduce deterioration involved in high-density multilayer woven fabrics.